Analysis of Caring Pattern for Persons with Schizophrenia in One Tumbon of Khon Kaen Province - Klungka, Sawinee; Piyabanditkul, Lukawee; Jaitieng, Arunnee (Nursing Science Journal of Thailand, 2022)
Purpose: To study the community care pattern for persons with schizophrenia and issues/concerns of care for persons with schizophrenia in the community. Design: Qualitative descriptive study. Methods: Purposive sampling was used. The informants consisted of 64 including 10 persons with schizophrenia, 15 caregivers of schizophrenia, 13 community leaders, 19 village health volunteers, 2 persons responsible for care of disadvantaged in Subdistrict Administration Organization and 5 healthcare workers. The data were collected by using in-depth interviews and data analysis. Main findings: The results showed that caring for schizophrenia patients in the community was relied mainly on family members especially the care for the activity of daily living. However, caregivers showed lack of the accurate knowledge and understanding about the disease. Home care provided by the primary health care workers under public health care system was available based on standardized practices. The basic welfare of patients remained unclear. Career building and support for joining other social activities were still lacking. Conclusion and recommendations: Results have shown that the scope and role of those involved in community care for persons with schizophrenia is unclear. Then, community nurses should development a care model for persons with schizophrenia including continuing care, referral and emergency management guidelines and the cooperation from network in order to provide care for persons with schizophrenia comprehensively leading to their better quality of life.